Validation of registration of pharmacological treatment in the Danish Hip and Knee Arthroplasty Registers. Issue 3 (4th November 2020) - Schelde, Astrid Blicher; Petersen, Janne; Jensen, Thomas Bo; Gromov, Kirill; Overgaard, Søren; Olesen, Jonas Bjerring; Jimenez‐Solem, Espen
Abstract: The aim of this study was to validate registration of pharmacological treatment in the Danish Hip Arthroplasty Register (DHR) and Danish Knee Arthroplasty Register (DKR). We conducted a population‐based study in the Capital Region of Denmark, January 2012 to April 2016. Positive predictive value (PPV) and sensitivity were calculated with 95% confidence intervals (CI) for antithrombotic, antihemorrhagic and antibiotic treatment registered in the DHR and DKR using electronic health records as the reference standard. For the DHR, the PPV and sensitivity were 77.9% (95% CI: 77.2‐78.6) and 99.6% (95% CI: 99.4‐99.7) for antithrombotic treatment, 70.9% (95% CI: 70.1‐71.7) and 97.4% (95% CI: 97.1‐97.7) for antihemorrhagic treatment, and 82.9% (95% CI: 82.2‐83.5) and 99.4% (95% CI: 99.3‐99.5) for antibiotic treatment, respectively. For the DKR, the PPV and sensitivity were 80.6% (95% CI: 79.8‐81.4) and 99.6% (95% CI: 99.4‐99.7) for antithrombotic treatment, and 84.4% (95% CI: 83.7‐85.1) and 100.0% (95% CI: 99.9‐100.0) for antibiotic treatment, respectively. The PPV and sensitivity for overall pharmacological treatment registered in the DHR and DKR were generally high and acceptable for use in research.